PERBANDINGAN LINGKAR BETIS DAN LINGKAR LENGAN ATAS SEBAGAI UKURAN PENGGANTI BERAT LAHIR [Comparison between Calf and Mid-Upper Arm Circumference Alternative of Birthweight Measurement] - Wahyu Kurnia Yusrin Putra; Kusharisupeni Kusharisupeni; Isna Aulia Fajarini (Media Gizi Indonesia, 2020)
High proportion of unmeasured birth weight as well as its improper documentation has become a problem in developing countries, including Indonesia. In 2017, a total of 9.9% labour were not assisted by health personnel and 43.4% of newborn did not have proper birth record. This condition increases the possibility of undetected low birth weight (LBW) cases. Therefore, this study aimed to determine an alternative measurement of birth weight which able to detect LBW. The study used cross sectional approach to analyse birth records from maternity clinic. A total of 100 records met the inclusion criteria, such as has complete record of birth weight, calf circumference, and mid-upper arm circumference (MUAC) which were measured within fi rst 24 hours of birth. Data was analysed using correlation test, area under curve (AUC), sensitivity, specifi city, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratio. Result showed that calf circumference and MUAC were signifi cantly correlated with birth weight (p <0.001) with r value 0.529 and 0.674 respectively. At cut-off value 10.62 cm, calf circumference had AUC 0.90, sensitivity 66.7%, specifi city 97.9%, PPV 8.2%, NPV 98.2%, likelihood ratio (+) 31.7 and likelihood ratio (-) 0.03. Calf circumference had better performance as alternative measurement of birth weight to detect LBW compared to MUAC.